Museum Theatre in Greece: Perspectives in Site Interpretation - Foteini Venieri; Niki Nikonanou (EXARC Journal)
The paper summarizes preliminary findings of a research project on the use of museum theatre in Greek open-air sites, as a part of a PhD thesis. The research focuses on the exploration of the development, use and function of museum theatre in Greek open-air sites based on available secondary resources and primary research, which included site visits, interviews and data analysis. The research summarized here was carried out in 2012 and presented in September 2012, in the OpenArch Conference "Museum interpretation and public engagement: Challenges and opportunities", in Höllviken, Sweden.